Globalisation in the Malaysian context : the experience of Malay adolescents with 'conduct disorders' : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Manawatū Aotearoa/New Zealand - Daud, Mohd Najmi (Massey University, 2017)
The process of globalisation offers opportunities for a country to progress to be a greater and more competitive nation. The Malaysian government is highly inspired by the concept of globalisation in progressing towards the vision of becoming a developed nation by the year 2020. Globalisation as a process is very demanding, requiring changes to the Malaysian political, cultural, economic, educational and social landscape. These changes have presented immense challenges to Malay adolescents where Western values have conflicted with traditional values and aspirations. Without adequate preparation, the potential incommensurability of values affects the locally defined wellbeing among Malay adolescents. Given that, how Malay adolescents understand and adapt to the globalisation process remains elusive. Therefore, this research is designed to explore the experiences of Malay adolescents who are considered to experience ‗conduct disorders‘ within the Malaysian context of globalisation. This research is a qualitative research inquiry, which utilised Interpretative Phenomenological Analysis (IPA) as a method of analysis. IPA is an approach that explores in detail personal lived experience to examine what the world is like from the point of view of the participants. Initial data was collected from 28 participants with 12 participants selected from a rehabilitation centre for young offenders in Malaysia for a more thorough analysis. The lived experience of the participants is presented and explained through three levels of analysis, the participants' demographic background and history, detailed life experiences of each case and finally, the meaning they attached to their experiences. The analysis suggests that the understanding of the Malay adolescents is constructed reflecting the changes in the dynamic of all segments of life alongside the emerging new lifestyles that are embedded in the processes of globalisation. Their lived experiences are described by referring to a complex relationship with and various tensions between different tenets. Those tenets include the traditional Malay cultures, values, beliefs and practices, which are much influenced by Islamic teaching, and the emergent new values and worldviews associated with globalisation and modernisation. Due to their vulnerability regarding self-characteristics, innate capabilities and the systemic flaws of relevant support systems, they are described as problematic in meeting the new, yet challenging environment. The participants lost their primary and reliable sources of survival. Instead, they are being introduced to various alternative resources that promote values and cultures that are against the normality of local practices. As a result, they end up in the criminal justice system. Realising that they have gone ―off track‖, the participants shared their intention to recover through various strategies, which include both action oriented and cognitive frameworks, but at the same time, they expected to face a range of hassles that may contribute to some difficulties for them to make progress. This research comes out with an argument that questions the appropriateness of the relevance of the diagnostic system of conduct disorders as defined in DSM. The experiences of the participants‘ suggested that they simply reacted to the changing context which offered immense challenges to their lived experiences. Therefore, rather than disordered the adolescents can be understood as responding to the conflicting conditions they face. Keywords: Malay adolescents, globalisation, conduct disorders, lived experiences, Interpretative Phenomenological Analysis
Keywords: Problem youth; Conduct disorders in adolescence; Social conditions; Malaysia; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology; Malay adolescents; Lived experiences; Interpretative Phenomenological Analysis; Globalisation